Zinc and other Micronutrients Supplementation through the use of Sprinkles: Impact on the Occurrence of Diarrhea and Respiratory Infections in Institutionalized Children - Danile L.B. Sampaio; Ângela P. De Mattos; Tereza Cristina M. Ribeiro; Maria Efigênia De Q. Leite; Conrad R. Cole; Hugo Costa-Ribeiro, Jr (Brazilian Society of Pediatrics, 2013)
Objective: To evaluate the incidence of diarrheal disease (DD) and acute respiratory infection (ARI) in children undergoing supplementation of zinc and other micronutrients through the use of sprinkles, as well as their acceptance by these participants. Method: This was a randomized double-blinded clinical trial of 143 healthy institutionalized children, aged 6 to 48 months. They were randomized into two groups and received daily zinc and micronutrients - test group (sprinkles), or micronutrients without zinc - control group. Children were supplemented for 90 days and followed regarding the outcomes of DD and ARI. Results: Of the randomized children, 52.45% belonged to the test and 47.55% to the control group. The incidence of DD in the test group was 14.7% and was 19.1% in the control group. The test group showed a lower risk of developing DD when compared to controls, but this finding was not statistically significant (RR = 0.77 [0.37 to 1.6], p = 0.5088). ARI had high incidence in both groups, 60% in the test group and 48.5% in the control group, with an increased risk of developing the disease in the test group, but with no statistical significance (RR = 1.24 [0.91 to 1.68], p = 0.1825). Regarding acceptance, the mean percentage of consumption, in days, of the entire content of the sachets containing sprinkles was 95.72% (SD = 4.9) and 96.4% (SD = 6.2) for the test and control groups, respectively. Conclusions: Zinc supplementation through the use of sprinkles did not reduce the incidence of DD or ARI among the evaluated children. The sprinkles were well accepted by all study participants.